Representasi Budaya Lokal dalam Musik Kontemporer Indonesia - Arido Laksono (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2020)
Current Indonesian contemporary music is characterized by the inclusion of elements of local culture which are able to present new nuances in the country's music trends. In fact, several songs written and produced by Indonesian musicians have been able to penetrate the realm of foreign music. Hence, it surely is an interesting phenomenon in the study of Indonesian popular culture. This short article will try to discuss the representation of local culture which has created new meanings for contemporary music trends in the country. The role of local language and the performance of the artists are considered to be influential factors of the trend. In addition, the advancement of information technology has accelerated the dissemination of popular culture products.